THE EFFECTS OF THE STUDENTS’ PERCEPTION ON LEARNING MEDIA AND PERSONALITY TOWARDS THE STUDENTS’ SPEAKING ABILITY - SUNARA SUNARA (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2018)
The aim of the research is to know the effects of the students’ perception on learning media and personality towards the students’ speaking ability. The total sample of this research is 82 students. The technique for collecting data of the students’ perception on learning media and personality used questionnaires, and the speaking ability test was acquired from the students’ speaking test by having 15- item interview instrument. The research methodology used is survey, and technique of data analysis used is regression analysis model. The statistic test used F-test, t-test, Rsquare and the data analysis used correlation technique and partial regression. The research findings are 1). There is significant effects of the students’ perception on learning media and personality jointly towards the students’ speaking ability at English education department students of private universities in Subang. The significance of regression coefficient equals to sig.0.000, or 0.000<0.05. The coefficient value of Fobserved equals to 11.555. It turns out that Fobserved > Ftabel, or 11.555>3.1, or H1 is accepted. RSquare coefficient equals to 0.226. It means that the variables of the students’ perception on learning media (X1) and personality (X2) jointly can determine or predict the speaking ability (Y) with contribution 22.6%. α equals to 0.05 and n equals to 82. H1 is rejected. 2). There is significant effects partially students’ perception on learning media towards the students’ speaking ability at English education department students of private universities in Subang. It declares that the sig value of students’ perception on learning media variable (X1) equals to 0.022. It shows that probability or significance is less than 0,05. The value of t coefficient or tobserved equals to 2.339, with ttable equals to 1.99. Since tobserved > ttable and the coefficient value of Sig.< 0,05, H1 is accepted. 3). There is significant effects partially personality towards the students’ speaking ability at English department students of private universities in Subang. It turns out that the sig. value of the personality variable (X2) equals to 0.001. It shows that probability or sig is less than 0,05. The value of t coefficient or tobserved equals to 3.394, with ttable equals to 1.99. Since tobserved > ttable and the coefficient value of Sig.< 0,05 here H1 is accepted